The Effect of Digital Literacy on Social Media Ethics - Fadhilah, Muhammad Naufal; Maryanti, Rini; Wulandary, Verra; Irawan, Asep Rudi (Jurnal Abdimas Kartika Wijayakusuma, 2022)
The lack of understanding of grade 9 students of junior high school, about digital literacy and social media ethics needs to be considered. This is because technology is increasingly sophisticated, making it easy for anyone to access it, including teenagers. By using a digital literacy assessment, researchers seek to increase understanding of social media ethics. The activity method used is google form with purposive sampling technique. Purposive sampling technique is a sampling technique based on characteristics to achieve the objectives of this study. The respondents were 10 students in grade 9 of junior high school, consisting of five male and five females. The questions given are in the form of 10 pre-test questions and 10 post- test questions. The results showed that respondents did not really understand social media ethics. However, after giving the material through digital literacy, the respondents showed a significant change. Respondents are also encouraged to start paying attention to social media ethics.